PRÁCTICAS Y EXPERIENCIAS DURANTE LA DIRECCIÓN DE LA TESIS EN LAS CIENCIAS DE LA SALUD. - CASTRO-RODRÍGUEZ, YURI (Revista Médica de Rosario)
Introduction: The elaboration of an academic thesis (dissertation, essay or degree work) is a complex process that is carried out with the guidance and orientation of a teacher. Objective: To collect original articles that has addressed the practices and experiences during thesis direction in health sciences programs. Methods: Systematized review study that searched for articles in the Scopus, MEDLINE and SciELO databases. The sources were searched during the last 10 years. We explored articles that described opinions of students or teachers, articles whose techniques collected scores, perceptions, perspectives or comments on the direction of the thesis. Results: Seventeen sources were found that met the selection criteria. Most were conducted in the Nursing (n = 4) and Medicine (n = 4) programs. With respect to experiences, four categories could be identified: accessibility and communication, control and commitment, trust and expectations, academic and work pressure. Regarding practices and strategies, six categories could be identified: feedback, meetings, group work, trainings, co-supervision, and work/academic inclusion. Conclusions: The experiences during the supervision of a thesis are varied, these include processes of control and commitment, creating trusting environments and establishing realistic expectations. Practices are multiple and the main ones include planning regular meetings, providing timely feedback and combining individual sessions with group sessions.